«Mitt namn er Petter Dass, som bur mot norskfagets ende» - Spaans, Ronny (Nordlit, 2022)
School reforms in recent decades, such as Kunnskapsløftet 2006, have expanded the Norwegian common core subject to include new text cultures and competence aims. A curriculum based on classic works of fiction is long gone. This development has had a twofold result on a historical author such as Petter Dass. On the one hand, we no longer read him as national literature; it may cause some teachers not seeing the value of teaching about the poet-priest at school. But on the other hand, new text cultures bring with them a softening of the traditional division between fiction and non-fiction. It has a fortunate effect: a rediscovery of the historical Petter Dass and new perspectives on Dass's poetry. In this article, I first examine rediscoveries of the historical authorship of Petter Dass, as Dass as a didactic and as an author of natural history. I then examine the presentation of the poet-priest in a selection of new textbooks for the school to see if any new insights of the poet-priest are included. The article shows both fortunate and unfortunate results in renewing the presentation of the renaissance poet in recent textbooks.